Conducting and Using Evaluability Assessments within CGIAR: CGIAR Evaluation Guidelines - CGIAR Independent Advisory and Evaluation Service (CGIAR Independent Advisory and Evaluation Service, 2022)
In 2022, the CGIAR System Council and Board approved a CGIAR Evaluation Framework and a revised Evaluation Policy. Their development followed a consultative, inclusive, and iterative approach that included strategic and operational discussions with, among others, CGIAR governance and management, the CGIAR Monitoring, Evaluation, and Learning Community of Practice (MELCOP), and an external peer review. The Evaluation Framework and Policy define evaluation as the systematic and objective assessment of an ongoing or completed project, program, initiative or policy, or operational modality in CGIAR, its design, implementation, and results. Rigorous, independent, external evaluations are foundational to CGIAR's effort to inform the design of interventions, provide actionable evidence to support management and governance decisions, and ensure a high level of accountability to donors. Meeting this potential, however, requires advanced planning and appropriate evaluative inputs.